2016
DOI: 10.1016/j.healthplace.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sector analysis of socioeconomic, racial/ethnic, and urban/rural disparities in food policy enactment in the United States

Abstract: We examined racial/ethnic, socioeconomic, and urban/rural disparities in food policy enactment across different sectors, as well as retail food access, throughout the United States. Policy and retail food store data were obtained from 443 communities as part of the Bridging the Gap Community Obesity Measures Project. Our results indicated that median household income was inversely associated with healthier retail food zoning policies in Hispanic communities, where competitive food policies for schools were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The positive effect of Hispanics is referred to as the "Hispanic paradox" in health, which is as yet not fully explained [55]. Health benefits start young, and it could be related to more access to fresh fruit and vegetables [24], and lower tobacco use [56] in Hispanic communities. The negative impact of non-Hispanic White poverty on health shows that the negative impact of poverty on health is more severe with the increase of rurality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive effect of Hispanics is referred to as the "Hispanic paradox" in health, which is as yet not fully explained [55]. Health benefits start young, and it could be related to more access to fresh fruit and vegetables [24], and lower tobacco use [56] in Hispanic communities. The negative impact of non-Hispanic White poverty on health shows that the negative impact of poverty on health is more severe with the increase of rurality.…”
Section: Discussionmentioning
confidence: 99%
“…Health disparities are partly a place-based issue embedded in the rural-urban divide [1,2]. This is especially the case for countries with sprawling and remote rural areas, such as Australia [18,23], Canada [12], and the US [2,19,24]. In the US, health disparities in rural communities are related to racial inequity, residential segregation and poverty [14,18], and income inequality [25,26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Taber et al reported that income was positively associated with the availability of healthy food outlets such as supermarkets, farmers markets and fruit/vegetable stands or carts which was associated with increased access to fruits and vegetables. 45 Therefore, limiting access to unhealthy foods in the classroom setting is critical to promote healthy eating, particularly for students with limited opportunities to consume healthy foods outside of school.…”
Section: Discussionmentioning
confidence: 99%
“…According to the US Census Bureau, approximately 47 million adults and 13.4 million children under 18 years reside in the rural USA (Ratcliffe et al, 2016). Evidence indicates many rural areas are affected by high rates of poverty, limited access to healthy and nutritious food, fewer grocery stores with fresh fruits and vegetables and easy access to fast-food restaurants when compared to urban areas (Connell et al, 2017; Popkin et al, 2012; Taber et al, 2016). As a result, rural families are less likely to meet dietary recommendations as they are forced to rely heavily on often expensive and none nutritious meals (Flegal et al, 2016; Story et al, 2002; Vandevijvere and Tseng, 2013; Yousefian Hansen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%